The role of ratio markers based on prealbumin in the diagnosis of periprosthetic joint infection - Cao, Qianqian; Ning, Xinchuang; Fan, Panlong; Cheng, Tianmiao; Zhang, Yuzhe; Cheng, Cheng; Dai, Zhipeng (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundPeriprosthetic joint infection (PJI) is a severe complication following total joint arthroplasty, and the timeliness of its diagnosis and treatment is crucial for patient recovery. Although various biomarkers have been extensively evaluated and applied in clinical practice, the diagnosis of PJI remains challenging. Therefore, it is necessary to identify more precise biomarkers for the diagnosis of PJI. This study aims to investigate the value of ratio-based biomarkers using prealbumin (PA) for the diagnosis of PJI.MethodsThis study compared the levels of C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), fibrinogen (FIB), PA, CRP/PA (CPR), ESR/PA (EPR), FIB/PA (FPR), and the combined ratio of CPR+EPR+FPR(CEF) in 180 patients with PJI and 105 patients with aseptic loosening (AL) who presented at our department from January 2019 to December 2024. The diagnostic efficacy of these markers in PJI diagnosis was assessed using the area under the curve (AUC) of the receiver operating characteristic (ROC) curve.ResultsAmong these biomarkers, CPR has the highest AUC of 0.921 (95%CI 0.890-0.952), and it can distinguish PJI with a cut-off value of 0.0366, a sensitivity of 76.1%, and a specificity of 95.2%. In the diabetic subgroup, the combined biomarker CEF has an AUC of 0.951 for diagnosing PJI, with a sensitivity of 88.9% and a specificity of 94.4%.ConclusionRatio-based markers based on PA show promise as valuable new adjunctive diagnostic markers for PJI.